Equation of the Standard EN 12195-1 Stipulates Unreasonable Demands for Cargo Securing - Juraj Jagelcak (Communications - Scientific letters of the University of Zilina, 2007)
Cargo securing is a factor influencing safety and quality of transport considerably. In this paper the problem of calculation of over top lashing to prevent tipping is mentioned. “European standard EN 12195-1 Load Restraint Assemblies. Safety. Part 1: Calculation of lashing forces” stipulates unreasonable demand for number of over top lashings to prevent tipping of load. The calculation of number of lashings gives infinite results for certain lashing angles. The reason can be found in equation (8) of the standard.